2009
DOI: 10.1016/j.sna.2008.05.028
|View full text |Cite
|
Sign up to set email alerts
|

Micromachined chip-scale plasma light source

Abstract: a b s t r a c tWe report on the microfabrication and testing of a chip-scale plasma light source. The device consists of a stack of three anodically bonded Pyrex wafers, which hermetically enclose a gas-filled cavity containing interdigitated Aluminum electrodes. When the electrodes are powered through an impedance matching circuit, these devices have been used to generate stable millimeter-size RF plasma discharges operating continuously for over 24 h in He or Ar at pressures ranging from 10 to 500 mbar at RF… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 20 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…In principle, a planar spiral coil can be deposited and patterned to inductively couple the plasma [20], but several hundred milliwatts of power will still be required for operation. dc glow discharges, although straightforward, with relatively simple design requirements for chip-scale clocks, need electrodes inside the lamp, allowing electrode erosion during operation and, hence, a shortened lifetime [15], [21]. other coupling techniques for discharge lamps, namely, the microwave [22] and the traveling wave discharges [16] also require high power (from a few watts to several hundreds of kilowatts) and are expensive, with very low efficiency when scaled down to chip-scale sizes [16].…”
Section: B Rb Plasma Light Sourcementioning
confidence: 99%
See 1 more Smart Citation
“…In principle, a planar spiral coil can be deposited and patterned to inductively couple the plasma [20], but several hundred milliwatts of power will still be required for operation. dc glow discharges, although straightforward, with relatively simple design requirements for chip-scale clocks, need electrodes inside the lamp, allowing electrode erosion during operation and, hence, a shortened lifetime [15], [21]. other coupling techniques for discharge lamps, namely, the microwave [22] and the traveling wave discharges [16] also require high power (from a few watts to several hundreds of kilowatts) and are expensive, with very low efficiency when scaled down to chip-scale sizes [16].…”
Section: B Rb Plasma Light Sourcementioning
confidence: 99%
“…such cells have been used as reference cells in miniaturize atomic clocks, but not as light sources-in part because of the additional complexity of igniting a stable plasma. although first studies on micro-cell plasma light sources reported on low-power rare-gas discharges, no rb light was reported [13]- [15]. here we present the design, fabrication, and characterization of a planar low-power microfabricated rb plasma light source emitting on the rb d1 and d2 lines.…”
mentioning
confidence: 98%
“…14) In contrast, micro-electro-mechanical systems (MEMS) technology has been utilized for making miniaturized plasma sources. [15][16][17][18][19] MEMS technology can be used to easily fabricate a structure on the order of 1-100 µm. However, generating plasma on the scale smaller than a cell has been still remained as a challenging task.…”
Section: Introductionmentioning
confidence: 99%
“…Once a transportable device was realized, the high reactivity of the plasma can be used where the plasma treatments are required. Among the broad applications, plasma light source is promising [1][2][3][4] because plasma can offer high-energy VUV photons that cannot be generated by LED and conventional lamps. For example, VUV emissions are used in absorption spectroscopy to measure the densities of ground state reactive species in the processing plasma [1,2].…”
Section: Introductionmentioning
confidence: 99%